A comparative study of small antenna efficiency measurements - Azremi, Abdullah Al Hadi; Shiraz, H.Ghafouri; Hall, Peter S. (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org